Side lobe suppression of Vivaldi antenna using shorting pin structure - Wee, F.H.; Yew, B.S; Siti Julia, Rosli; Siti Nur Ainni, Dzaaba; Lee, Yeng Seng (2017)
This paper was executed in order to design side lobe suppression of Vivaldi antenna using shorting pin structure at S-band frequency. Nowadays, Vivaldi antenna has been used to satellite communications, remote sensing and radio telescope. There are a variety of designs such as tapered slot Vivaldi antenna, antipodal Vivaldi antenna and balanced antipodal Vivaldi antenna. Tapered slot Vivaldi antenna has been selected to design the project. The design of the antenna is start with patch antenna by using basis of transmission line model (TLM) formula to calculate the length and width of the patch. It is shaped into Vivaldi antenna. For the final design, the shorting pin structure will connect the patch on top side and the ground plane to absorb the unbalanced current. The shorting pin will reduce the side lobe. The antenna was simulated by using CST Microwave Studio. Based on the simulation results, the Vivaldi antenna shows a good performance as the return loss less than − 10 dB, voltage standing wave ratio, gain, directivity and radiation pattern was obtained the desired result as for a resonant frequency of 3 GHz. The radiation pattern of Vivaldi antenna with shorting pin structure reducing as compared with the design without shorting pin structure. The final antenna design shows that it has a few main lobe magnitudes where the antenna can focus and direct the energy for transmission or receiving of the energy signal.